Hospital-acquired and zoonotic bacteria from a veterinary hospital and their associated antimicrobial-susceptibility profiles: A systematic review - Sebola, Dikeledi C.; Oguttu, James W.; Kock, Marleen M.; Qekwana, Daniel N. (Frontiers in Veterinary Science, 2023)
Hospital-acquired infections (HAIs) are associated with increased mortality, morbidity, and an economic burden due to costs associated with extended hospital stays. Furthermore, most pathogens associated with HAIs in veterinary medicine are zoonotic. This study used published data to identify organisms associated with HAIs and zoonosis in veterinary medicine. Furthermore, the study also investigated the antimicrobial-susceptibility profile of these bacterial organisms. A systematic literature review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-analyses” (PRISMA) guidelines. Search terms and five electronic databases were used to identify studies published over 20 years (2000-2020). The risk of bias was assessed using the “Strengthening the Reporting of Observational Studies in Epidemiology-Vet” (STROBE-Vet) checklist. Out of the identified 628 papers, 27 met the inclusion criteria for this study. Most studies (63%, 17/27) included were either from small animal or companion animals’ clinics/hospitals, while 5% (4/27) were from large animal clinics inclusive of bovine and equine medicine. Hospital-acquired bacteria were reported from environmental surfaces (33.3%), animal clinical cases (29.6%), and fomites such as cell phones, clippers, stethoscopes, and computers (14.8%). Staphylococcus spp. was the most (63%; 17/27) reported organism, followed by Escherichia coli (19; 5/27), Enterococcus spp. (15%, 4/27), Salmonella spp. (15%; 4/27), Acinetobacter baumannii (15%, 4/27), Clostridioides difficile (4%, 1/27), and Pseudomonas aeruginosa (4%; 1/27). Multidrug-resistant (MDR) organisms were reported in 71% (12/17) of studies linked to Methicillin-resistant Staphylococcus aureus (MRSA), Methicillin-resistant Staphylococcus pseudintermedius (MRSP), Enterococcus spp., Salmonella Typhimurium, A. baumannii, and E. coli. The mecA gene was identified in both MRSA and MRSP, the blaCMY-2 gene in E. coli and Salmonella spp., and the vanA gene in E. faecium isolate. Six studies reported organisms from animals with similar clonal lineage to those reported in human isolates. Organisms associated with HAIs and zoonosis have been reported from clinical cases, environmental surfaces, and items used during patient treatment and care. Staphylococcus species is the most reported organism in cases of HAIs and some isolates shared similar clonal lineage to those reported in humans. Some organisms associated with HAIs exhibit a high level of resistance and contain genes associated with antibiotic resistance.